Offspring of Mothers With Histories of Chronic and Non-chronic Depression: Symptom Trajectories From Ages 6 to 15 - Silver, Jamilah; Olino, Thomas M.; Carlson, Gabrielle A.; Klein, Daniel N. (Frontiers in Psychiatry, 2020)
Several studies have reported that individuals with chronic depression have higher rates of depressive disorders, and particularly chronic depression, in their first-degree relatives, compared to those with non-chronic (episodic) major depression. In addition, a few studies have suggested that offspring of parents with chronic depression have elevated rates of depression and other psychopathology. Most of this work uses the Diagnostic and Statistical Manual of Mental Disorders (DSM), which defines chronicity as persistence for at least 2 years. An alternative is a life-course, approach, which evaluates overall course since first onset. We examined the trajectories of depressive, anxiety, and externalizing symptoms in a community sample of 577 offspring of mothers with histories of chronic depression, non-chronic (or episodic) major depression, and no depression using prospective, multi-informant assessments from age 6 to age 15. Offspring of mothers with a history of depression exhibited higher levels of depression, anxiety, and externalizing symptoms than offspring of mothers who were never depressed. Moreover, the effects of maternal depression on offspring depression, anxiety, and externalizing symptoms were more pronounced for mothers with histories of chronic than non-chronic depression, particularly when the life-course approach to classifying chronicity was used. These data suggest that research that combines chronic and non-chronic depressions includes significant heterogeneity that may hinder understanding of etiology and reduce the likelihood of developing a cumulative and replicable literature. . In addition, these findings have significant implications for prevention and treatment.